2004
DOI: 10.1146/annurev.phyto.42.012604.135455
|View full text |Cite
|
Sign up to set email alerts
|

MICROBIAL DIVERSITY IN SOIL: Selection of Microbial Populations by Plant and Soil Type and Implications for Disease Suppressiveness

Abstract: An increasing interest has emerged with respect to the importance of microbial diversity in soil habitats. The extent of the diversity of microorganisms in soil is seen to be critical to the maintenance of soil health and quality, as a wide range of microorganisms is involved in important soil functions. This review focuses on recent data relating how plant type, soil type, and soil management regime affect the microbial diversity of soil and the implication for the soil's disease suppressiveness. The two main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
776
1
40

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,249 publications
(844 citation statements)
references
References 121 publications
27
776
1
40
Order By: Relevance
“…Another study conducted in the carbonate-rich soil (pH 8.5) using 16S rRNA clone library analysis showed that Pseudomonas and Lysobacter genera constituted 45% of the total bacterial abundance in the maize rhizosphere (García-Salamanca et al, 2013). Though exact mechanisms for such differences are not completely understood, because these studies were all conducted on different soil types, it is likely that soil type may be one of the most important environmental variables influencing the structure of the maize root-inhabiting bacterial community at low taxonomic levels (Berg and Smalla, 2009;Castellanos et al, 2009;Garbeva et al, 2004). Growth-stage related dynamics and the differences in rhizosphere bacterial community structure from different soil types further support the general concept that plant and soil type cooperatively shape the structure of microbial community in the rhizosphere (Berg and Smalla, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in the carbonate-rich soil (pH 8.5) using 16S rRNA clone library analysis showed that Pseudomonas and Lysobacter genera constituted 45% of the total bacterial abundance in the maize rhizosphere (García-Salamanca et al, 2013). Though exact mechanisms for such differences are not completely understood, because these studies were all conducted on different soil types, it is likely that soil type may be one of the most important environmental variables influencing the structure of the maize root-inhabiting bacterial community at low taxonomic levels (Berg and Smalla, 2009;Castellanos et al, 2009;Garbeva et al, 2004). Growth-stage related dynamics and the differences in rhizosphere bacterial community structure from different soil types further support the general concept that plant and soil type cooperatively shape the structure of microbial community in the rhizosphere (Berg and Smalla, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, relative totals may not demonstrate huge changes but may reflect changes in specific groups of organisms (Curl and Truelove 1986). It is not known whether subtle but statistically significant shifts in one or more factors would have at least minor impact on crops in the field (Degens et al 2001;Garbeva et al 2004). Nonetheless, small differences (less than 10-fold) should be biologically interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…A diversidade de microrganismos é fundamental para a manutenção da saúde e da qualidade do solo, estando envolvida em importantes funções desse ecossistema (GARBEVA et al, 2004). Entre os organismos funcionais do solo e associados ao sistema radicular, destacam-se os fungos micorrízicos arbusculares (FMA), pertencentes ao filo Glomeromycota, com 230 espécies descritas (OEHL et al, 2011).…”
Section: Introductionunclassified